Islamic Values in Muslim Housing Griya Sakinah Residence and Influence on the Behaviour of Its Residents - Mohammad Sahid Indraswara; Gagoek Hardiman; R Siti Rukayah; Fahmi Syarif Hidayat (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
The development of housing that carries Islamic values has grown rapidly in the last 10 years in line with the increasing economic potential and awareness of Muslims to get a conducive environment for families, making developers build housing with Islamic concepts. This study aims to determine Islamic values that are embodied in the area, housing units and determine their influence on the behavior of its inhabitants. The research method used is descriptive analytical, namely revealing facts on objects in the present time. The results showed that the Griya Sakinah Muslim housing applied Islamic values to the area, facilities and housing units, namely the Hablumminallah in the form of a mosque which functions as a worship space and socialization space for residents of housing and local residents. The value of Hablumminannas is manifested in the construction of public facilities in the area and Hablumminalalamien is manifested in the construction of gardens in housing and the form of residential units with tropical architectural concepts in accordance with the local climate and environment. What has not been noticed is the value of death reminders in the form of tombs for residential residents. The new thing found in this study is the role of mosques to overcome social segregation in housing areas with cluster concept and further research needed about hijab in Islamic settlement.